Korelasi Kepribadian Fear Missing Out terhadap Adiksi Impulsive Online Buying di Masa Pandemi Pada Anak dan Remaja - Eka Sri Handayani; Rudy Haryadi (Kuras Institute, 2022)
FOMO is the worry, anxiety, or fear that a person experiences when he is not involved in an event, experience, or conversation in his social environment. A person with FOMO syndrome can have an impact on health. However, making purchases based purely on emotional needs creates the possibility of buying things that are not needed and can become uncontrollable behavior. The aim of this study was to find out that FOMO personality has a significant relationship with impulsive online buying addiction during a pandemic in adolescents at Alalak 1 high school. Test the hypothesis of this study using the Product Moment correlation technique. This test examines the relationship between FOMO personality (X) and impulsive online buying addiction (Y). The results of data calculations use the product moment correlation formula to find out how significant the correlation coefficient is between variable X and variable Y. Through these calculations, an r count of 0.616 is obtained with a significant level of 5%, an r table of 0.197 is obtained, which confirms that Fomo has a significant relationship to Addiction Impulsive online buying.